(untitled) (Journal of actual problems of jurisprudence, 2018)
This article discusses actual problems of legal provision of veterinary safety of Kazakhstan. The work presented in some detail the factors veterinary safety, which should be considered when building a development strategy. The paper presents a detailed analysis of national legislation and practice in the study area, as well as its conclusions on the improvement of legislation that govern social relations in the field of veterinary security of the Republic of Kazakhstan. Key words: veterinary safety, agriculture, food security, agricultural policy.